Impact of redox-related genes on tumor microenvironment immune characteristics and prognosis of high-grade gliomas - Yuan, Yunbo; Zuo, Mingrong; Zhang, Shuxin; Chen, Siliang; Feng, Wentao; Wang, Zhihao; Chen, Mina; Liu, Yanhui (Frontiers in Cellular Neuroscience, 2023)
High-grade glioma (HGG) defines a group of brain gliomas characterized by contrast enhancement, high tumor heterogeneity, and poor clinical outcome. Disturbed reduction–oxidation (redox) balance has been frequently associated with the development of tumor cells and their microenvironment (TME). To study the influence of redox balance on HGGs and their microenvironment, we collected mRNA-sequencing and clinical data of HGG patients from TCGA and CGGA databases and our own cohort. Seventy-five redox-related genes (ROGs) were found to be differentially expressed between HGG and normal brain, and consensus clustering using the expression profile of ROGs divided the both IDH-mutant (IDHmut) and IDH-wildtype (IDHwt) HGGs into subclusters with different prognosis. Functional enrichment analysis revealed that the differential aggressiveness between redox subclusters in IDHmut HGGs were significantly associated with cell cycle regulation pathways, while IDHwt HGG redox subclusters showed differentially activated immune-related pathways. In silico TME analysis on immune landscapes in the TME showed that the more aggressive redox subclusters in both IDHmut and IDHwt HGGs may harbor a more diverse composition of tumor-infiltrating immune cells, expressed a higher level of immune checkpoints and were more likely to respond to immune checkpoint blockade. Next, we established a glioma-ROG expression risk signature (GRORS) which showed AUCs of 0.787, 0.884, and 0.917 in predicting 1, 2, and 3-year survival of HGG patients in the held-out validation datasets, and the C-index of a nomogram combining the GRORS and other prognostic information reached 0.835. Briefly, our results suggest that the expression pattern of ROGs was closely associated with the prognosis as well as the TME immune profile of HGGs, and may serve as a potential indicator for their response to immunotherapies.